2009
DOI: 10.1063/1.3156314
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl sulfide isotopologues: Ultraviolet absorption cross sections and stratospheric photolysis

Abstract: Ultraviolet absorption cross sections of the main and substituted carbonyl sulfide isotopologues were calculated using wavepacket dynamics. The calculated absorption cross section of (16)O(12)C(32)S is in very good agreement with the accepted experimental spectrum between 190 and 250 nm. Relative to (16)O(12)C(32)S, isotopic substitution shows a significant enhancement of the cross section for (16)O(13)C(32)S, a significant reduction for (18)O(12)C(32)S and (17)O(12)C(32)S and almost no change for the sulfur i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 38 publications
4
36
0
Order By: Relevance
“…The TDMs for the two 1 A states are much smaller than μ A and therefore the contributions of these states to the absorption cross section are small. The TDMs μ A and μ B calculated by Suzuki et al 26 and Danielache et al 40 are qualitatively and quantitatively similar to those shown in Fig. 8.…”
Section: Transition Dipole Moment Functionssupporting
confidence: 73%
See 2 more Smart Citations
“…The TDMs for the two 1 A states are much smaller than μ A and therefore the contributions of these states to the absorption cross section are small. The TDMs μ A and μ B calculated by Suzuki et al 26 and Danielache et al 40 are qualitatively and quantitatively similar to those shown in Fig. 8.…”
Section: Transition Dipole Moment Functionssupporting
confidence: 73%
“…10) and in striking contrast to N 2 O, σ A , and σ B are completely smooth. The calculated A state cross section of Suzuki et al 26 shows very intense and very dense structure, while the cross section calculated by Danielache et al 40 shows almost no structure except at high excitation energies at the edge of the absorption band (E ph > 49 000 cm −1 ). In the present study, only the cross sections for the quasi-bound states C, c, and d show vibrational resonance structure.…”
Section: B State-resolved Cross Sectionsmentioning
confidence: 91%
See 1 more Smart Citation
“…Jørgensen et al (2008) used the potential energy surfaces of Suzuki et al (1998) and found that 34 S enrichment is very small. A similar result was obtained by Danielache et al (2009) using different potential energy surfaces. The latter study also considered 13 C fractionation and found photolysis to greately deplete OCS in 13 C which contradicts recent experimental results of Hattori et al (2011).…”
Section: Introductionsupporting
confidence: 73%
“…In the model, no isotopic fractionation is assumed for any reactions except for SO2 photolysis, for example, OCS photolysis is not associated with large isotopic fractionation (37). This assumption is probably not correct, although SO2 photolysis is often the rate limiting step for sulfate production in a reducing atmosphere, and hence likely controls the isotopic composition of aerosols (2)(3)(4)(5).…”
Section: Atmospheric Composition ( )mentioning
confidence: 99%